Rupture of Baker's cyst producing pseudothrombophlebitis in a patient with Reiter's syndrome - Ozgocmen, Salih; Kaya, Arzu; Kocakoc, Ercan; Kamanli, Ayhan; Ardicoglu, Ozge; Ozkurt-Zengin, Fatma (Elsevier (Singapore) Pte Ltd, 2004)
This is an unusual case of pseudothrombophlebitis resulting from rupture of Baker's cyst in a patient with Reiter's syndrome. The patient presented with a swollen, painful left calf and persistent itching on the skin of the calf. Ultrasonography showed a ruptured popliteal cyst with minimal hemorrhage and fluid collection within the fascial compartments and gastrocnemius muscle. Color Doppler ultrasound showed a patent popliteal vein and artery and duplex Doppler scans revealed a normal flow pattern. In conclusion, the clinical picture of deep vein thrombosis and that of pseudothrombophlebitis are difficult to distinguish by clinical examination and necessitate detailed examination by imaging techniques. Persistent pruritus on calf skin resulting from irritation of inflammatory synovial fluid may be an important clinical feature.
Keywords: Baker's cyst; Popliteal; Pseudothrombophlebitis; Rupture; Ultrasonography